The Improvement of Final Mixing Workstation Based on Recommended Weight Limit (RWL) and Workplace Ergonomics Risk Assessment (WERA) Methods - Arisandi, Diki; Peprizal; Firdaus, Muhamad Rifqy; Prayoga, Muhamad Rizal; Juraida, dan Anita (International Journal of Psychosocial Rehabilitation, 2020)
Musculoskeletal Disorders (MSDs) are disorder that caused by accumulation of injuries or damages in musculoskeletal system due to repetitive trauma, thus forming a considerable damage with symptoms related to muscle tissues, tendons, ligaments, cartilages, nervous system, bone structures and blood vessels. The problem in this research is the work such as repeatedly moving and processing raw materials in machines, causing complaintts of pain and aches from the operator in parts of the body such as neck, hands, waist and legs. Method used in this research is the Recommended Weight Limit (RWL) and Workplace Ergonomics Risk Assessment (WERA) Methods. RWL method is a recommended load limit that can be lifted by humans without causing injury even though the work was done repetitively and in sufficiently long time, whereas WERA is a survey tool that developed for screening task in order to expose physical risk factors related to Work-related Musculoskeletal Disorders (WMSDs). The resulting score of WERA in this research is 36, where that value is deemed safe risk level (Medium), whereas the initial RWL calculation result shows that LI = 1.996 > 1, which means the risk of work of lifting raw materials into the mixer is risky so it may cause irritation in MSDs. After the repairs done using supporting tools to reduce the load of lifting raw materials into the mixer obtained RWL score of LI = 0.85 < 1, so it can be concluded that the work activity turned out safe or not at risk.